Service Provision in Distribution Channels. (October 2022) - Gurnani, Haresh; Singh, Shubhranshu; Tang, Sammi; Wang, Huaqing
Consumers may need help using an inherently complex product after purchase. This article studies a manufacturer's and a retailer's incentives to provide presales service and after-sales support in a distribution channel. The authors consider a model in which a manufacturer makes wholesale price and channel service decisions. Subsequently, a retailer makes retail price and channel service decisions. They find that, in equilibrium, both channel members provide presales service. If the fixed-cost investment needed to enhance the effectiveness of after-sales support is small, the manufacturer lets the retailer provide after-sales support. Yet when it is above a threshold and the retailer becomes unwilling to invest in providing after-sales support, the manufacturer steps in and does so. As expected, when the fixed cost is too large, the manufacturer also opts out of providing after-sales support. Interestingly, when the retailer provides after-sales support, the level of presales service and the demand for after-sales support can simultaneously be the highest among all configurations. Finally, the authors demonstrate the robustness of their main results by studying alternative channel service configurations.